Identification and distribution of South Africa's non-native beachfleas (Crustacea: Amphipoda: Talitridae) - Diemer, Natalie (Marine Research (MA-RE) Institute, 2016)
The two introduced beachfleas Orchestia gammarellus and Platorchestia platensis reported from South Africa have complicated histories, filled with misidentification and inaccurate documentation of distribution records. At the outset of this study, records of Orchestia gammarellus were restricted to - Langebaan Lagoon, Knysna and Milnerton Lagoon; while Platorchestia platensis had been recorded from Knysna and '34°S/19°E' (Gansbaai area). To verify this information, historical records were re-examined and 16 estuaries and lagoons in the Western Cape and two in the Eastern Cape Province were searched in order to determine the correct historical and current distributions of both species. It was found that historically and still today O. gammarellus occurs in Langebaan Lagoon. Its other current known distribution is the Berg River Estuary, Milnerton Lagoon and the Bushman's River; it never occurred in Knysna and records from that site were misidentifications of P. platensis. Historic records could only confirm P. platensis in Knysna and one other unknown location (specimen apparently mislabelled). Current searches conversely found P. platensis to be wide-spread, its range extending from Langebaan Lagoon to Algoa Bay (regions east of Bushman's River were not searched). Both species were described morphologically in detail taking their growth patterns into account and highlighting their differences, allowing for easier identification.